On The Nullity of Generalized Rooted T-Tuple With B-Bridge Coalescence Graphs - Ibrahim, Nechirvan B. (Science Journal of University of Zakho, 2016)
In this paper, we determine the nullity of generalized rooted t-tuple coalescence graphs and the nullity of generalized rooted t-tuple with b-bridge coalescence graphs. Finally, the nullity of generalized rooted t-tuple with b-path coalescence graph and (b-bridge)-tuple coalescence graph and nullity of (b-path)-tuple coalescence graph is obtained for some special types of graphs.